Minimal residual disease (MRD) in non‐Hodgkin lymphomas: Interlaboratory reproducibility on marrow samples with very low levels of disease within the FIL (Fondazione Italiana Linfomi) MRD Network. Issue 4 (16th August 2019) - Della Starza, Irene; Cavalli, Marzia; De Novi, Lucia Anna; Genuardi, Elisa; Mantoan, Barbara; Drandi, Daniela; Barbero, Daniela; Ciabatti, Elena; Grassi, Susanna; Gazzola, Anna; Mannu, Claudia; Agostinelli, Claudio; et al.
Abstract: In 2009, the four laboratories of the Fondazione Italiana Linfomi (FIL) minimal residual disease (MRD) Network started a collaborative effort to harmonize and standardize their methodologies at the national level, performing quality control (QC) rounds for follicular lymphoma (FL) and mantle cell lymphoma (MCL) MRD assessment. In 16 QC rounds between 2010 and 2017, the four laboratories received 208 bone marrow (BM) samples (126 FL; 82 MCL); 187 were analyzed, according to the EuroMRD Consortium guidelines, by both nested (NEST) polymerase chain reaction (PCR) and real‐time quantitative (RQ) PCR for BCL2/IGH MBR or IGHV rearrangements. Here, we aimed at analyzing the samples that challenged the interlaboratory reproducibility and data interpretation. Overall, 156/187 BM samples (83%) were concordantly classified as NEST+/RQ+ or NEST−/RQ− by all the four laboratories. The remaining 31 samples (17%) resulted alternatively positive and negative in the interlaboratory evaluations, independently of the method and the type of rearrangement, and were defined "borderline" (brd) samples: 12 proved NEST brd/RQ brd, 7 NEST−/RQ brd, 10 NEST brd/RQ positive not quantifiable (PNQ), and 2 NEST brd/RQ−. Results did not change even increasing the number of replicates/sample. In 6/31 brd samples, droplet digital PCR (ddPCR) was tested and showed no interlaboratory discordance. Despite the high interlaboratory reproducibility in the MRD analysis obtained and maintained by the QC round strategy, samples with the lowest MRD levels can still represent a challenge: 17% (31/187) of our samples showed discordant results in interlaboratory assessments, with 6.4% (12/187) remained brd even applying the two methods. Thus, although representing a minority, brd samples are still problematic, especially when a clinically oriented interpretation of MRD results is required. Alternative, novel methods such as ddPCR and next‐generation sequencing have the potential to overcome the current limitations.